2020
DOI: 10.1097/brs.0000000000003654
|View full text |Cite
|
Sign up to set email alerts
|

Shilla Growth Guidance Compared With Magnetically Controlled Growing Rods in the Treatment of Neuromuscular and Syndromic Early-onset Scoliosis

Abstract: Study Design. Retrospective review of consecutive series of patients treated at two institutions. Objective. The aim of this study was to compare the health-related quality of life (HRQoL) and surgical outcomes of Shilla growth guidance and magnetically controlled growing rod (MCGR) treatment in patients with syndromic and neuromuscular early-onset scoliosis (EOS). Summary of Background Data. Knowledge of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 28 publications
2
20
0
Order By: Relevance
“…As in the main texts, the data were not separated out, so we included them in the TGR group, as the vast majority were treated with this system. Papers by Akbarnia et al [ 10 ], Bachabi et al [ 11 ], Haapala et al [ 12 ], Andras et al [ 13 ], and Luhmann et al [ 14 ], dealt with comparisons between TGR and MCGR, TGR, and VEPTR, Shilla and MCGR, and TGR and Shilla, respectively, so they appear in the table for the applicable system. The demographic findings of the included articles are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As in the main texts, the data were not separated out, so we included them in the TGR group, as the vast majority were treated with this system. Papers by Akbarnia et al [ 10 ], Bachabi et al [ 11 ], Haapala et al [ 12 ], Andras et al [ 13 ], and Luhmann et al [ 14 ], dealt with comparisons between TGR and MCGR, TGR, and VEPTR, Shilla and MCGR, and TGR and Shilla, respectively, so they appear in the table for the applicable system. The demographic findings of the included articles are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The complication rate was as high as 111% of the patients (39%-192%), and the complication rate per surgical procedure was 54%. Haapala et al [ 12 ] showed the fewest complications – 39%. The remaining authors assessed the number of complications at a similar level.…”
Section: Discussionmentioning
confidence: 99%
“…Early-onset scoliosis (EOS) is a progressive disorder that includes complex curvatures of the pediatric spine related to different etiologies (idiopathic, congenital, syndromic, and neuromuscular) in children younger than 10 years. If left untreated, EOS in these patients may lead to poor respiratory and cardiac development and progressive deformities and cause complex and difficult-to-treat spinal problems [1][2][3]. Currently, surgical treatments with growth-preserving instrumentation (GPI) techniques without growth arrest are preferred in cases of high-angle and progressive EOS.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of EOS surgery is to avoid postoperative complications when selecting the appropriate GPI for the patient. Many multicenter studies have compared the advantages and disadvantages of different growth-friendly techniques [1,[13][14][15].Similar to other techniques, various problems may occur as a result of Shilla application. The Shilla technique aims to avoid these problems and the problems caused by active lengthening procedures.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of these technologies in recent studies has been limited to younger patient populations, [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] with current indications in the US limited to patients with early-onset scoliosis (<10 years of age), 32,33 and while these technologies allow fusion to be delayed until skeletal maturity is reached, a final fusion procedure is still required.…”
mentioning
confidence: 99%